BH LYN: UBVRI AND CCD PHOTOMETRY OF THE ECLIPSING CATACLYSMIC VARIABLE - Andronov, I. L; Kolesnikov, S. V.; Niarchos, P. G.; Shakhovskoy, N. M.; Zola, S. (Одеські астрономічні публікації, 2017)
We report preliminary results of the UBVRI photoelectric and R CCD observations obtained in the Crimean astrophysical observatory and the Astronomical observatory of the Athens University. The light curve represents well-pronounced eclipses with a total duration of the most sharp phase of 0.d022. At the eclipse, the color index U-B becomes smaller by 0.m2 than outside eclipse, contrary to other colors, where the color indices become larger. This indicates a presence of uneclipsed source of ultraviolet emission, possibly the wind from the accretion disc.